1986
DOI: 10.1002/ccd.1810120211
|View full text |Cite
|
Sign up to set email alerts
|

New balloon catheter for prolonged percutaneous transluminal coronary angioplasty and bypass flow in occluded vessels

Abstract: A new balloon catheter was developed for continuous perfusion of coronary arteries during angioplasty (CPC catheter). Steerable Grüntzig balloon catheters (3.7 mm) with two lumina were formed. The first lumen was used for balloon inflation. Side holes to the second lumen proximally and distally to the balloon were created for coronary perfusion even during inflation phase. At a perfusion pressure of 120 mmHg, a flow rate of 63 +/- 3 ml/min with 0.9% saline and 43 +/- 1 ml/min with plasma expander were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

1987
1987
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 23 publications
0
10
0
4
Order By: Relevance
“…Several such perfusion systems have been used experimentally and clinically and have proved to be effective in reducing acute myocardial ischemia.8-" However, such perfusion systems are complex and cumbersome. Erbel et al 20 have reported results in five dogs and 11 patients with an autoperfusion-type catheter; prolongation of time from onset of dilatation to appearance of ischemia was noted in three of the dogs and eight of the patients. Their catheter had a larger profile and fewer sideholes, which may account for some of the difference in results.…”
Section: Discussionmentioning
confidence: 95%
“…Several such perfusion systems have been used experimentally and clinically and have proved to be effective in reducing acute myocardial ischemia.8-" However, such perfusion systems are complex and cumbersome. Erbel et al 20 have reported results in five dogs and 11 patients with an autoperfusion-type catheter; prolongation of time from onset of dilatation to appearance of ischemia was noted in three of the dogs and eight of the patients. Their catheter had a larger profile and fewer sideholes, which may account for some of the difference in results.…”
Section: Discussionmentioning
confidence: 95%
“…7). Clearly, myocardial perfusion and reduction of ischemia, both of which have been amply demonstrated to occur with the Erbel-type catheter [2][3][4], are preferable to the absence of antegrade coronary flow that occurs during standard balloon inflations. However, the requirement for a large lumen and the retraction and replacement of the guidewire during procedures performed with conventional perfusion devices are limitations that may, in part, explain why these catheters are not used in favor of nonperfusion devices.…”
Section: Discussionmentioning
confidence: 99%
“…Autoperfusion catheters are available and have been clearly shown to limit myocardial ischemia during bal-loon inflation [2][3][4]. The limitation of ischemia can reduce the risk of complex angioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Possible solutions include shortening of imaging times with the use of ultrafast echoplanar data acquisition strategies 24 or the use of tunneled balloon designs. 25 With such a continuous perfusion catheter, dilation times for PTCA could be significantly increased. 25 MRI of vascular walls can also be accomplished with external surface coils.…”
Section: Discussionmentioning
confidence: 99%
“…25 With such a continuous perfusion catheter, dilation times for PTCA could be significantly increased. 25 MRI of vascular walls can also be accomplished with external surface coils. 26 The relatively poor results obtained in this study primarily reflect differences in the animal model: Whereas Skinner et al 26 used a deendotheliazation model resulting in well-developed atherosclerotic plaque, this study included rabbits with very early-stage disease.…”
Section: Discussionmentioning
confidence: 99%